O kształtowaniu kulturowego oblicza cieszyńskiej ziemi - Kadłubiec, Karol Daniel (Górnośląskie Studia Socjologiczne. Seria Nowa, 2021)
The article addresses the following topics: Cieszyn Silesia and its location at the crossroads of the most important trade and cultural routes, and their cultural significance, monastic and princely settlement; Vlachs as carriers of linguistic and cultural influences; the migration of the natives of Cieszyn motivated by the need to find work; the contacts of Cieszyn craftsmen with the neighboring regions and the consequences of these contacts in the sphere of cultural tradition.